(untitled) (Journal of Bio-Science, 2018)
To analyze the effect of different pruning operation on the incidence and severity of different diseases of tea (Camellia sinensis) plant. An experiment was carried out at the Bilashchara Experimental Farm of Bangladesh Tea Research Institute (BTRI), Srimangal. Three places of the sections were selected randomly that received LP (Light Prune), DSK (deep skiff), MSK (medium skiff) and LSK (light skiff) operations. Every bush was critically observed before and after pruning operations and all infected diseases were recorded. Disease severity was expressed as percent disease index (PDI). MSTAT program was used for statistical snalysis. After pruning operation, maximum incidence 33.33% and severity 8.20% of Grey brown blight was found in LSK. Horse hair blight maximum incidence (18%) and maximum severity (6.27%) both were found in LSK. In thread blight maximum incidence was in MSK 22.67% and maximum severity was 7% in LSK. The highest % reduction of branch canker both in incidence and severity was observed in LP section followed by DSK, MSK and LSK. In case of Gall disease maximum incidence and severity both was LSK 24.67% and 7.60%. The highest incidence of black rot was in LSK 41.33% and severity 12.87% was in MSK. From the study, it was recommending that without using any chemicals, only by different pruning operations and proper cleaning can reduce the in incidence and severity of those diseases. J. bio-sci. 24: 01-09, 2016